PENGARUH IKATAN HUBUNGAN TERHADAP KESETIAAN PELANGGAN - Sri Vandayuli Riorini (Media Riset Bisnis & Manajemen, 2009)
This research explains about the effects of three relationship bondings, namely financial bonding, social bonding and structural bonding to consumer's trust that will lead to the commitment of the consumers and ultimately will affect the loyalty of the consumers.Data was gathered by distributing questionaire to 100 respondents who have been a student in their course center. The sampling technique used was a purposive sampling. The analysis tool used was Structural Equation Modeling using Amos version 16 software. .The hypotesis testing result showed that among three relationship bondings, the bonds that has a significant effect to trust are social bonding and structural bonding, whereas financial bonding has no effect to the trust of consumers. Trust also has a significant effect to commitment and ultimately the commitment has an effect to loyalty.It is highly recommended to explore another services industry beside education industry for the next research and possibly to add other variables which may have any effect to the variables observed by this current research.Keywords : Relationship bonding, Trust, Commitment, Loyally